Planting seeds: a state of the question on sexuality in training in biological sciences (Research, Society and Development, 2020)
The current work aims to analyze what exists about the teaching of sexuality in the initial teaching formation in Biological Sciences. The methodology chosen was the State of the Question (EQ), in which we used the search service for job disclosure portals: BDTD (Digital Library of Theses and Dissertations), the CAPES Portal and the biennial event ENALIC (National Meeting of Bachelors). At the end of the search process, a total of eight works was selected to compose the EQ. Among the results, we highlight that the South Region appears with a greater number of published works and women stand out in the authorship. In addition to these findings, we can conclude that EQ is a method of bibliographic research that contributes to a better relationship between researchers and the objectives and themes chosen for the development of research like those investigated.